CSR Activities of International Ice Hockey Clubs - Márton, Laura (International Journal of Engineering and Management Sciences, 2022)
Worldwide there is a growing ephasis on corporate social responsibility (CSR) and became increasingly important for sports organisations too. At the same time the international research and study numbers increasing, which examine the practical application of the CSR concept in sport.The study provides an insight into the importance of CSR activities in foreign hockey clubs, especially in Finnish and Swedish hockey clubs with long-rooted hockey cultures, through expert interviews and their analysis. We get an answer for how they have integrated environmental activities and helping society into their every day live. Good examples from abroad are provided, ont he basis of which this study can help the hungarian sport clubs who want to develop their organisation through CSR activities.